Targeting adenosine enhances immunotherapy in MSS colorectal cancer with EGFRvIII mutation - Jing Wu; Yang Zhao; Min Shi; Yong Li; Yu Jiang; Fei Sun; Jianjun Peng; Jiao Wang; Qiong Huang; Na Huang; Yawen Wang; Yulu Shi; et al. (Journal for ImmunoTherapy of Cancer)
Background Patients with microsatellite stable (MSS) colorectal cancer (CRC) often display resistance to immunotherapy. Epidermal growth factor receptor (EGFR)-targeted therapies have shown potential in enhancing immunotherapy, yet clinical benefits remain unfulfilled, which may relate to inadequate patient stratification.Methods Circulating tumor cells and tumor tissues were collected from multicenter cohorts of patients with CRC receiving cetuximab to analyze EGFR variant type III (EGFRvIII) expression and immune infiltration. Syngeneic mouse models of EGFRvIII CRC were used to investigate the combined efficacy of adenosine inhibition and antiprogrammed cell death protein 1 (anti-PD-1).Results EGFRvIII mutations are found in about 10% of MSS CRC and are associated with poor response to cetuximab therapy. EGFRvIII-mutated patients with CRC exhibit an adenosine-mediated immunosuppressive tumor microenvironment (TME) subtype. Combination therapy with adenosine inhibitors remodels the TME, reversing cetuximab resistance and enhancing anti-PD-1 efficacy in EGFRvIII CRC.Conclusions Our findings identified EGFRvIII-positive CRC as a distinct subtype characterized by adenosine-mediated immunosuppressive TME. Targeting adenosine significantly improved the efficacy of anti-PD-1 in MSS CRC.